Single‐Walled Carbon Nanotubes as an Additive in Organic Photovoltaics: Effects on Carrier Generation and Recombination Dynamics. Issue 4 (28th January 2022) - Abudulimu, Abasi; Eckstein, Klaus; Gemayel, Mirella El; Namal, Imge; Phillips, Adam B.; Ellingson, Randy J.; Heben, Michael J.; Hertel, Tobias; Meier, Sebastian B.; Lüer, Larry
Abstract : Employing single‐walled carbon nanotubes (SWNTs) as an additive in the active layer of organic photovoltaics (OPV) to improve charge extraction is gaining weight in the research community. While SWNTs can transport charge carriers orders of magnitudes faster than conventional polymers, they also quench excitons and trap‐free charges, reducing device performance. Such influences of SWNTs on OPV device performance remain inadequately explored and incompletely understood. Herein, the impact of SWNTs, enriched in (6, 5) chirality, on the charge generation and extraction properties of two different OPV devices is studied by femtosecond‐microsecond transient absorption spectroscopy and transient photovoltage/photocurrent techniques. It is shown that depending on the donor material properties (e.g., energetics), SWNTs can reduce carrier generation by quenching the excitons and increase carrier recombination through trapping processes. Then, by performing an analytical calculation of the current–voltage characteristics of the devices using the parameters determined via the transient measurements, it is shown that the increased recombination also relates to morphological changes induced by the SWNTs. These results shed light on the performance limiting factors of the SWNTs when incorporated into the active layer of the solar cells. This work thus can accelerate the blend optimization process for high‐performance organic solar cells. Abstract : Single‐walled carbon nanotubes are promising candidates for enhancing charge extraction in organic solar cells due to their exceptional charge transport properties. However, being defect prone and randomly oriented in the active layer crossing multiple donor‐acceptor phases, they can also reduce device performance by quenching excitons and trapping charge carriers in a time scale from femtoseconds to microseconds.